Epidemiology of childhood acute leukemias in marginalized populations of the central-south region of Mexico: results from a population-based registry - Flores-Lujano, Janet; Allende-López, Aldo; Duarte-Rodríguez, David Aldebarán; Alarcón-Ruiz, Erika; López-Carrillo, Lizbeth; Shamah-Levy, Teresa; Cebrián, Mariano E.; Baños-Lara, Ma. del Rocío; Casique-Aguirre, Diana; Elizarrarás-Rivas, Jesús; López-Aquino, Javier Antonio; Garrido-Hernández, Miguel Ángel; et al. (Frontiers in Oncology, 2024)
Aranguré44, 45** and Juan Carlos Núñez-Enriquez1,39** Puebla, Tlaxcala and Oaxaca, respectively. B-cell acute lymphoblastic leukemia was the most common subtype across the three states.The incidence of childhood AL in the central-south region of Mexico is within the range of rates reported in other populations of Latin American origin. Two incidence peaks were identified for lymphoblastic and myeloid leukemias. In addition, differences in the incidence of the disease were observed among state subregions which could be attributed to social factors linked to the ethnic origin of the inhabitants. Nonetheless, this hypothesis requires further investigation.